ANALISIS STRUKTUR RANGKA BATANG 2D DENGAN METODE MATRIKS KEKAKUAN MENGGUNAKAN APLIKASI PTC MATHCAD DAN ANALISIS SAP2000 - Muhammad yazid; Rizki Ramadhan Husaini; Sukri Sukri; Deri Islami; Teddy Julio Gunawan; Muhammad Defri Wahyudi (Racic : Rab Construction Research, 2023)
The analysis of a 2-dimensional truss structure (plane truss) can be done using the matrix method with the stiffness matrix formula to obtain the internal forces that occur. The stiffness matrix method can be easily described with the PTC Mathcad application. With this PTC Mathcad application, the stages in the matrix method analysis can be clearly seen, starting from the stages of the matrix method, namely creating a truss model, creating a local stiffness matrix, creating a transformation matrix, creating a global stiffness matrix, compiling a structural stiffness matrix, stacking partitions and re-arrangement of structural stiffness matrices, calculating displacement in local and global coordinates, calculating the forces in each rod and calculating the reaction force of the platform. The purpose of this research is to create a simple program using the PTC Mathcad programming language to analyze the 2-dimensional truss and compare the results of the simple programming with the results of the SAP2000 analysis. The comparison results obtained on the joint displacement / displacement value and the bar force value between the PTC Mathcad application and SAP2000 obtained an average result below 2%. For the analysis of the reaction to the pedestal, the analysis using PTC Mathcad is the same as the SAP2000 analysis for the vertical reaction and for the horizontal direction, the SAP2000 application gets the result of 1.25x10-13 while in PTC Mathcad there is none.